Requirements for troubleshooting wi-fi network security through location technologies - Macia, Nicolás
The location of mobile devices in a network can be used to provide services that locate users as well, making positioning and tracking of mobile devices. From the standpoint of security and network administration, the location of mobile devices can be used as a protective mechanism complementary to existing ones, either by detecting unauthorized access to the Wi-Fi network as well as allowing the tracking of stolen mobile computers. The aim of this paper is to study techniques for locating mobile devices in Wi-Fi environments and discuss countermeasures that can be used by users who want to avoid being located. Based on this, will select the most appropriate location technique taking into account the countermeasures discussed. It will analyze the feasibility of implementing location technologies with general purpose hardware, evaluating possible changes to the software needed for access points so as to permit use in the tracking system. From this, we propose a location system architecture taking into account the appropriate security requirements to perform access control to information obtained and to safeguard the privacy and anonymity of the same.